Adolescent Girls' and Boys' Science Peer Relationships and Perceptions of the Possible Self as Scientist. - Stake, Jayne E.; Nickens, Shannon D. (Sex Roles, 2005)
Girls' tend to have less peer support for their science interests than do boys, which may contribute to gender differences in science motivation. The effect of science peer relationships on adolescents' visions of their possible personal future lives as scientists was studied in 161 female and 163 male gifted high school students who participated in summer science enrichment programs. Student reports of having positive science peer relationships were associated with more positive expectations of the possible personal self as scientist prior to the programs, and both program-related and nonprogram-related science peer relationships were associated with changes in the possible self at posttesting and at 6 month follow-up. These relations held for both male and female students. At follow-up, girls reported a stronger social niche with fellow program participants and stronger science peer relationships than did boys. Implications of the findings are discussed within the larger gendered societal context for science achievement. Reprinted by permission of the publisher.